ICULTOURE.ID Sebagai Media Pendukung Pembelajaran Bahasa Indonesia Terintegrasi Pengenalan Budaya - Purwono, Prahoro Yudo (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
This research aims to develop a virtual learning platform that integrates Indonesian language learning with the introduction of Indonesian culture called